Risk Analysis Methodology associated to public procurement processes - Carranza Alvarado, Kacerine (2022)
As in all human activity, public contracting has risks associated that, according to the current Costa Rican legislation, must be properly managed to establish security on each purchase process, however, it is not a common practice. This article proposes a methodology for risk analysis in public procurement that is divided into two parts: the first one includes a general analysis of the risks associated with the contracting process that is proposed to be developed once a year. The second part shows a simpler and more practical methodology for risk analysis and management on each contracting process. Finally, an example of how to use this methodology is presented in order to show how practical and applicable it is on both goods and services procurement process.